The role of philanthropic education in enhancing religious sociality at MI Muhammadiyah 4 Jetis - Riyadi Riyadi; Aldo Redho Syam; Syamsul Arifin; Miftah Hur Rahman Zh; Hendro Risbiyantoro; Rokimin Rokimin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This research aims to further explore the role of philanthropic education in shaping students' characters and supporting the implementation of the scholarship program at MI Muhammadiyah 4 Jetis. The research investigates how philanthropic values such as empathy, solidarity, and social responsibility are integrated into the educational process, particularly through teacher involvement and the scholarship program. Using a qualitative case study approach, data were gathered through interviews, observations, and documentation involving teachers, students, and school administrators. The findings reveal that philanthropic education, implemented through both classroom activities and community projects, plays a significant role in shaping students' character, fostering social awareness, and promoting a sense of responsibility. The scholarship program, which combines financial support with initiatives like peer assistance and social engagement, further strengthens students' commitment to their community. In conclusion, this study highlights the effectiveness of philanthropic education in developing both academic and moral values, offering a model for other institutions aiming to integrate character-building into their curricula.